R -v- Ingram, C., Ingram, D. and Whittock, T. The Who Wants to be a Millionaire? fraud trial - French, Peter; Harrison, Philip (International Journal of Speech, Language and the Law, 2004)
The television show, ‘Who Wants to be a Millionaire?’ (WWTBM) was created in the UK by the independent production company Celador in 1998. It is a general knowledge quiz show in which contestants have the chance to win a top prize of one million pounds. The programme has reached its fifteenth series in the UK and it runs several nights a week on the independent television network. It has been exported to over 100 countries worldwide. In March and April of 2003 two contestants and an accomplice were tried and convicted of attempting to defraud the programme of the million pound prize. Their strategy involved the contestant, after having been asked the questions, ‘thinking aloud’ about possible answers whilst an accomplice in the studio guided him towards the correct one by a system of coughing. This report describes the methods used by the authors to determine from the recordings of the programme where in the studio the coughing was coming from.